Cal Poly Marching Band (1973)
Marching band spelling out 'USA' with their hats and forming a shield shape around it. This photo was likely taken when the Cal Poly Marching Band performed at at the Oakland Coliseum November 4, 1973 during the pregame and halftime of the Raiders-New York Giants game.